(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2025)
Advance care planning is a widely underutilized practice in clinical settings. This gap in practice highlights the need to explore further how patients, families, and the healthcare team engage in shared decision-making as a process aimed at promoting patient autonomy within a relational dynamic experienced in the therapeutic context. From this perspective, the focus of this analysis concerns disagreement and potential conflict within care relationships, which are strongly marked by the gap between hypothetical scenarios and actual decision-making processes in clinical practice. Starting from the description of a clinical case, this analysis aims to promote strategies to make advance care planning a valuable and effective tool in clinical practice to prevent conflicts, which encourages patients to discuss their desires, preferences, and choices to facilitate patient engagement and to simplify and support the medical decision-making process.